Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1136/bmjopen-2018-027752
|View full text |Cite
|
Sign up to set email alerts
|

Association of the combination of weight gain after 20 years of age and current obesity with chronic kidney disease in Japan: a cross-sectional study

Abstract: ObjectivesWeight gain after 20 years of age is associated with chronic kidney disease (CKD). However, the impact of weight gain on CKD might differ by current obesity status. We investigated the association of the combination of weight gain after 20 years of age and current obesity with CKD among adults in Japan.DesignA cross-sectional study.Setting and participantsWe analysed data from 94 822 adults aged 40–64 years who had an annual health check-up in Japan from April 2013 to March 2014.Primary outcome measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…For example, in a cohort of healthy men, Ryu and colleagues found a U‐shaped distribution between weight change and CKD risk, which was heightened with both weight loss and weight gain [33]. In a study of 94,288 Japanese adults, Ochaiai and colleagues showed that the association between weight gain and CKD risk was higher among those with obesity than those with normal weight [34]. With weight gain, both glomerular filtration rate and renal plasma flow must increase, and this may lead to compensatory hypertrophy of the glomerular capillary, glomerular tuft, and renal tubules.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a cohort of healthy men, Ryu and colleagues found a U‐shaped distribution between weight change and CKD risk, which was heightened with both weight loss and weight gain [33]. In a study of 94,288 Japanese adults, Ochaiai and colleagues showed that the association between weight gain and CKD risk was higher among those with obesity than those with normal weight [34]. With weight gain, both glomerular filtration rate and renal plasma flow must increase, and this may lead to compensatory hypertrophy of the glomerular capillary, glomerular tuft, and renal tubules.…”
Section: Discussionmentioning
confidence: 99%
“…Because 35,017 participants with missing data were excluded from the analysis, 94,893 participants were analyzed in this study. The present study was a cross-sectional survey that used the data including the study subjects, and several studies that used the data have been reported [9][10][11][12][13][14][15].…”
Section: Methodsmentioning
confidence: 99%
“…Blood glucose, hemoglobin A1c (HbA1c), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), triglyceride (TG), ALT, AST, and SCr levels were measured within 24 hours of blood collection. The detail of the measurements was described in our previous studies [9][10][11][12][13][14][15]. The estimated glomerular filtration rate (eGFR) was calculated with the following formula: eGFR = 194 × SCr ðmg/dLÞ −1:094 × age ðyearsÞ −0:287 ðif female × 0:739Þ [16].…”
Section: Data Collectionmentioning
confidence: 99%
“…On the other hand, weight gain generally tends to accrue in middle age regardless of race or gender. 7 Long-term weight gain during adulthood has been linked to increased risks of metabolic syndrome (MetS), 8 chronic kidney disease, 9 hypertension, 10 non-alcoholic fatty liver disease (NAFLD), 11 sleep disturbance, 12 and dyslipidemia, 13 independently of the peak BMI level reached. These widespread findings are in agreement with the results of studies conducted in Asian populations.…”
Section: Introductionmentioning
confidence: 99%